The sum of a number and seven times of it is equal to the product of 25.6 and 12.5. What will be one fourth of that number?

Answers

Answer 1
Answer:

Answer:

x + 7x = (25.6)(12.5)

8x = 320

x = 40, so (1/4)(40) = 10


Related Questions

Evaluate 5x – 2 when X = 3
How do you change a fraction into a decimal
A boat costs $19,200 and decreases in value by 12% per year. How much will the boat be worth after 5 years?
Describe how to decide if 94 is a prime number or composite number
How do u write 4,000,000+3,000+50+2 in standard form

Round 0.01123 to the nearest hundredth?

Answers

the answer to your question would be 0.01
The answer is 0.01 going by decimal places. Decimal places always beging with tenths then proceed to hundredths, thousandths and so forth

Jose asks his friends to guess the higher of two grades he received on his math tests. He gives them two hints. The difference of the two grades is 16. The sum of one-eighth of the higher grade and one-half of the lower grade is 52. The system that represents his scores is below.. . x – y = 16. . x + y = 52. . What is the higher grade of Jose’s two tests?. . 48.
52.
80.
96

Answers

x - y = 16
1/8 x + 1/2 y = 52   / * 2 ( multiply both sides by 2 )
-------------------------
      x - y = 16
+
1/4 x + y = 104 
----------------------
 1.25 x = 120
   x = 120 : 1.25
   x = 96
 Answer: D ) 96

your answer sould be the last option (D) 96

What is A2 – (B + C) in simplest form?A=8x2 – 25x + 7
B=8x2– 25x + 11
C=10x2 – 25x + 7
D=10x2 – 25x + 11

A, B, and C are polynomials, where:
A = 3x – 4
B = x + 7
C = x2 + 2

Answers

A2 - (B + C) = (3x - 4)2 - ((x + 7)+ (x2 + 2))
A2 - (B + C) = 9x2 - 24x + 16 - (x2 + x + 9)
A2 - (B + C) = 9x2 - 24x + 16 - x2 - x - 9
A2 - (B + C) = 8x2 - 25x + 7

So, the answer is
A:
8x2 – 25x + 7

Answer: 8x^2 - 25x + 7

Step-by-step explanation:

Here, A = 3x - 4, B = x + 7 and C = x^2 + 2

A^2 - (B + C)= (3x-4)^2-(x+7+x^2+2)     ( By putting the values)

= (3x)^2+ (4)^2- 2* 3x* 4- x- 7 - x^2 -2    ( solving the brackets)

=  9x^2+ 16 - 24x - x- 7 - x^2 -2

=  8x^2- 25x + 7        ( By operating like terms)

A^2 - (B + C) = 8x^2- 25x + 7

Thus, Option A is correct.

What is 1725 with a 15% markup

Answers

\begin{array}{|c|ll} \cline{1-1} \textit{\textit{\LARGE a}\% of \textit{\LARGE b}}\n \cline{1-1} \n \left( \cfrac{\textit{\LARGE a}}{100} \right)\cdot \textit{\LARGE b} \n\n \cline{1-1} \end{array}~\hspace{5em}\stackrel{\textit{15\% of 1725}}{\left( \cfrac{15}{100} \right)1725}\implies 258.75~\hfill~\underset{ \textit{marked up} }{\stackrel{ 1725~~ + ~~258.75 }{\text{\LARGE 1983.75}}}

Answer:

1983.75

Step-by-step explanation:

What is 1725 with a 15% markup?

15% = 0.15

We take

1725 + (1725 x 0.15) = 1983.75

So, the answer is 1983.75

When 9 ^2/3 is written in simplest radical form, which value remains under the radical?3
6
9
27

Answers

Answer
The value under the radical is 3

Explanation
9^(2/3) This means 9 squared then find find the cube root of the answer.

9^(2/3)=∛(9^2 )
= ∛81 
∛(3×3×3×3) = ∛(3)³ ₓ ∛3
= 3∛3
The value under the radical is 3

I hope this now shows clearly the number under the radical is 3. 

Answer:

The value remains under the radical is 3

Step-by-step explanation:

Given the expression 9^{(2)/(3)}

We have to find the value remains under the radical.

9^{(2)/(3)}

It can be written as\sqrt[3]{9^2}

\sqrt[3]{81}

\sqrt[3]{3* 3* 3* 3}

3\sqrt[3]{3}

Hence, the value remains under the radical is 3

For two functions, f(x) and g(x), a statement is made that f(x) = g(x) at x = 5. What is definitely true about x = 5?

Answers

Answer:

At x= 5 the value of both function are equal.

Step-by-step explanation:

Given that two function f(x) and g(x)

And at  x=5  

f(x)=g(x)

It means when we put x=5 in the function f(x) then we get some value and when we put x= 5 in the function g(x) then we get the same value .

Hence , the value of both function at x=5 are equal and we can say that both function intersect at the point (5,0).For example,

Let we take f(x)=x-5

and g(x)=5-x

Put  x=5 in the function f(x) then we get

f(x)=5-5=0

Now we put x=5 in the function g(x) then we get

g(x)=5-5=0

Hence, we get same value for both function .

When x = 5 then the function f(x) and g(x) are equal so when you insert 5 into the two functions, you will get the same answers for both of the functions.